2012
DOI: 10.1186/1471-2342-12-7
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the ultrasound technique to measure the rectus femoris muscle diameter in older CAD-patients

Abstract: BackgroundThe increasing age of coronary artery disease (CAD) patients and the occurrence of sarcopenia in the elderly population accompanied by 'fear of moving' and hospitalization in these patients often results in a substantial loss of skeletal muscle mass and muscle strength. Cardiac rehabilitation can improve exercise tolerance and muscle strength in CAD patients but less data describe eventual morphological muscular changes possibly by more difficult access to imaging techniques. Therefore the aim of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
104
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(111 citation statements)
references
References 15 publications
4
104
1
2
Order By: Relevance
“…Finally, Thomaes et al (2012) Other studies comparing MRI and RUSI measures of different muscles have shown good results but differing analytical techniques limits the comparison to the present study. The CSA of lumbar multifidus was compared using MRI and RUSI at vertebral levels from L2 to S1 and no significant differences were found, despite differences in position for imaging (Hides, Richardson, 1995).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Finally, Thomaes et al (2012) Other studies comparing MRI and RUSI measures of different muscles have shown good results but differing analytical techniques limits the comparison to the present study. The CSA of lumbar multifidus was compared using MRI and RUSI at vertebral levels from L2 to S1 and no significant differences were found, despite differences in position for imaging (Hides, Richardson, 1995).…”
Section: Discussionmentioning
confidence: 81%
“…Three previous studies have compared measures taken from US and MRI images of the quadriceps muscle group (Walton, Roberts, 1997, Reeves, Maganaris, 2004, Thomaes, Thomis, 2012. Direct comparison to the present study is limited for two of these studies (Walton, Roberts, 1997, Reeves, Maganaris, 2004, as they compared CSA rather than linear measurements using a compound scanning technique (Cavalieri technique).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Therefore, minimal changes in TC are likely clinically relevant. Ideally a CT scan would have been utilised to confirm true changes in limb circumference under this cadaver model (Thomaes et al, 2012), but this was cost prohibitive for the scope of this study. When interpreting our study results, one should also consider that long-haired dogs were used for evaluation of hair clipping; therefore the findings may not be applicable to short-haired dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Definitive measurement of muscle mass involves advanced imaging, making it impractical and cost prohibitive in most clinical cases. Limb circumference measurement with a tape measure is frequently used in both human and veterinary patients as an indirect measure of changes in muscle mass over time (Doxey, 1987a, Doxey, 1987b, Jarvela et al, 2002, Thomaes et al, 2012).…”
Section: Introductionmentioning
confidence: 99%